Pengaruh Kepemimpinan Kepala Sekolah dan Beban Kerja Guru terhadap Kinerja Guru di SMKN 1 Puloampel - Ramdan; Sakti Andayani; Fuad Abdul Baqi; Andriani Sariwardani (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Vocational education requires teachers with optimal performance in order to produce graduates who are competent and prepared to face the demands of the workforce. Teacher performance is influenced by various factors, including principal leadership and teacher workload, both of which are directly related to the implementation of instructional duties and school administration. This study focuses on the influence of principal leadership on teacher performance, the influence of teacher workload on teacher performance, and the simultaneous influence of both variables on teacher performance at SMKN 1 Puloampel. The study employed a quantitative method with a descriptive survey approach involving 55 teachers selected through a total sampling technique. Data were collected through observation and questionnaire distribution using a Likert scale and were subsequently analyzed using the t-test and F-test with the assistance of IBM SPSS Statistics 24.0. The findings revealed that principal leadership did not have a positive and significant effect on teacher performance, whereas teacher workload had a positive and significant effect on teacher performance. Simultaneous testing further indicated that principal leadership and teacher workload collectively did not exert a significant effect on teacher performance. These findings demonstrate that teacher performance is more strongly influenced by internal factors such as professional competence, work motivation, teaching experience, and task management abilities. The novelty of this study lies in the finding that a proportionally organized teacher workload is capable of enhancing teachers’ discipline, responsibility, and work effectiveness, while principal leadership has not yet demonstrated a significant influence on teacher performance within the vocational school environment. This study contributes to the development of vocational education management through the strengthening of teacher professionalism and balanced workload management.